=3z(2z2-9z+4)
2007-01-15 03:11:34
·
answer #1
·
answered by srinu710 4
·
0⤊
2⤋
6z3 – 27z2 + 12z
First notice that 3z is common to all 3 terms so factor it out:
3z(2z^2 -9z +4)
Now see if you can factor (2z^2 -9z+4). You can, getting:
3z(2z-1)(z-4)
2007-01-15 03:23:30
·
answer #2
·
answered by ironduke8159 7
·
0⤊
0⤋
The roots of 10x² + 2x - 8 = 0 are x1 = -a million and x2 = 4/5 => 10x² + 2x - 8 = 10*(x+a million)*(x-4/5) = (x+a million)*(10x-8) ============ different possibilities are: 10x² + 2x - 8 = (2x+2)(5x-4) or 10x² + 2x - 8 = (5x+5)(2-8/5) and so on.
2016-10-31 04:05:00
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
First divide by the common factor, 3z
3z(2z^2 - 9z + 4)
Then do FOIL, starts like this you can fill in the rest:
3z(2z - .... )(z - .....)
2007-01-15 03:08:50
·
answer #4
·
answered by hayharbr 7
·
0⤊
1⤋
Take 3z common.
3z(2z^2-9z+4)=0
So either z=0 or 2Z^2-9z+4=0
2z^2-8z-z+4=0
2z(z-4)-1(z-4)=0
(2z-1)(z-4)=0
so z=1/2 or z=4
So factors are z=0,z=1/2,z=4
2007-01-15 03:12:06
·
answer #5
·
answered by Tariq M 3
·
0⤊
2⤋
3z(2z2-9z+4)
3z (z-4 )( 2z-1 )
2007-01-15 03:11:45
·
answer #6
·
answered by italianwiseass13 2
·
0⤊
0⤋
factor out z
solve as quadradic
ans 0,0.5,4
2007-01-15 03:16:49
·
answer #7
·
answered by CubicleWizard 2
·
0⤊
1⤋
3z(2z-1)(x-4)
2007-01-15 03:12:47
·
answer #8
·
answered by Steve A 7
·
0⤊
1⤋